Infection with Drechslera hawaiiensis. Case report and literature review - Álvarez, Jaime (Revista Estomatología, 2011)
This article reports an orofacial infection caused by Drechslera hawaiiensis that normally is mortal to the patient. The case was surgically treated in Cali - Colombia in 1984 by teeth removal, and osteototomy of affected bone in the hard palate and the base of the vomer bone. Twenty years later the patient resulted infected by Dreschslera curvularia but survived both infections. A literature review (Pubmed - 2011) showed that only another case report by Drechslera hawaiiensis the patient survived. This other case was reported in the Anderson Hospital Institute in 1984. It is unknown if there is a chronic infection stage and the transmission mode of this pathogen. In patients with chronic symptoms affecting the paranasal sinuses and nasal cavity it is possible to suspect this rare disease. Key words: Oral facial infection, mycotic infection, Drechslera hawaiiensis.